Case study on the effects of a disability inclusive mindset in a large biotechnology company. Issue 1 (3rd September 2021) - Ochrach, Chase; Thomas, Kathryn; Phillips, Brian; Mpofu, Ngonidzashe; Tansey, Tim; Castillo, Stacie
Abstract : Purpose: Employers increasingly seek a competitive advantage through inclusive hiring practices and recruitment of persons with disabilities. Early research indicates when employers consider individuals for their strengths rather than solely for their needs, the organization prospers. However, details about how companies pursue a disability inclusive workplace and the effect of those efforts are poorly understood. Design/methodology/approach: An inductive qualitative case study approach was utilized to understand one biotechnology corporation and their approach to recruiting, hiring, and retaining employees with disabilities. Individual and focus group interviews were conducted. Findings: Results suggest that when the company lives its mission around wellness and inclusivity, they benefit from working with and learning from a range of perspectives, furthering their growth. Placing equal emphasis on hiring a diverse workforce and prioritizing supports and wellness practices lead to greater productivity and innovation. Practical implications: This study illustrates how one company successfully recruits and hires persons with disabilities, resulting in benefits to their financial bottom line and to the organizational culture. Originality/value: This paper offers insights for other companies intentionally hiring persons with disabilities, providing accommodations in the workplace, and creating an organizational culture where all employees feel valued and supported. These steps have a direct impact on employee engagement, productivity, and retention.